Retrotransposition of Long Interspersed Element 1 Induced by Methamphetamine or Cocaine - Okudaira, Noriyuki; Ishizaka, Yukihito; Nishio, Hajime (The Journal of biological chemistry, 2014)
Long interspersed element 1 (L1) is a retroelement constituting ∼17% of the human genome. A single human cell has 80–100 copies of L1 capable of retrotransposition (L1-RTP), ∼10% of which are “hot L1” copies, meaning they are primed for “jumping” within the genome. Recent studies demonstrated induction of L1 activity by drugs of abuse or low molecular weight compounds, but little is known about the underlying mechanism. The aim of this study was to identify the mechanism and effects of methamphetamine (METH) and cocaine on L1-RTP. Our results revealed that METH and cocaine induced L1-RTP in neuronal cell lines. This effect was found to be reverse transcriptase-dependent. However, METH and cocaine did not induce double-strand breaks. RNA interference experiments combined with add-back of siRNA-resistant cDNAs revealed that the induction of L1-RTP by METH or cocaine depends on the activation of cAMP response element-binding protein (CREB). METH or cocaine recruited the L1-encoded open reading frame 1 (ORF1) to chromatin in a CREB-dependent manner. These data suggest that the cellular cascades underlying METH- and cocaine-induced L1-RTP are different from those behind L1-RTP triggered by DNA damage; CREB is involved in drug-induced L1-RTP. L1-RTP caused by drugs of abuse is a novel type of genomic instability, and analysis of this phenomenon might be a novel approach to studying substance-use disorders.